Studying public policy - "Howlett, Michael" (Ontario, 2009)
Studying Publisc Policy develops an analytical framework of the subject for students in public policy course. Instead of focussing on the substantive policy of a particular policy area, the book examines the theoretical and conceptual foundations of, and approaches used in, the policy sciences.
Keywords: Public Policy